2015
DOI: 10.1063/1.4929728
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-cBN alloy: A universal cutting material

Abstract: Diamond and cubic boron nitride (cBN) as conventional superhard materials have found widespread industrial applications, but both have inherent limitations. Diamond is not suitable for high-speed cutting of ferrous materials due to its poor chemical inertness, while cBN is only about half as hard as diamond. Because of their affinity in structural lattices and covalent bonding character, diamond and cBN could form alloys that can potentially fill the performance gap. However, the idea has never been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Ir 2 P was synthesized using a mixture of Ir powder (purity 99.9%) and red phosphorus powder (purity 99.999%) with a molar ratio of Ir : P = 2 : 1 under high pressure/temperature conditions. The syntheses were carried out in a two-stage multi-anvil apparatus based on a DS 6 × 8 MN cubic press 41 42 and a Walker-type multianvil press at Arizona State University 43 . The 14/8 sample assembly, consisting of a 14 mm (edge length) MgO octahedron, a ZrO 2 thermal insulator and a Ta heater, was compressed by eight cubic WC anvils, each with 8-mm corner truncation (edge-length).…”
Section: Methods Summarymentioning
confidence: 99%
“…Ir 2 P was synthesized using a mixture of Ir powder (purity 99.9%) and red phosphorus powder (purity 99.999%) with a molar ratio of Ir : P = 2 : 1 under high pressure/temperature conditions. The syntheses were carried out in a two-stage multi-anvil apparatus based on a DS 6 × 8 MN cubic press 41 42 and a Walker-type multianvil press at Arizona State University 43 . The 14/8 sample assembly, consisting of a 14 mm (edge length) MgO octahedron, a ZrO 2 thermal insulator and a Ta heater, was compressed by eight cubic WC anvils, each with 8-mm corner truncation (edge-length).…”
Section: Methods Summarymentioning
confidence: 99%
“…Structure refinements were performed using Pawley method [35]. High-pressure electrical resistance (ER) was measured using a quasi-four-probe resistance measurement system consisting of a Keithley 6221 current source, a 2182A nanovoltmeter and 7001 voltage/current switch system in a DAC and a cubic large-volume press (LVP) [36][37][38]. Photocurrent measurements of powder and single-crystal samples were performed using an Autolab PGSTAT128N workstation to keep track of the current-time (I-t) data [38].…”
Section: A In Situ High-pressure Characterizationsmentioning
confidence: 99%
“…Huang et al 15 applied molecular dynamics simulations for the responses of c-BN lms under nanoindentation, and found that during the indentation, plastic deformation of c-BN is can mainly be attributed to stress-induced slips of dislocations along {111}<110> orientations. In addition, Wang et al 16 reported the synthesis and characterization of transparent bulk diamond/c-BN alloy, and showed that the alloy has a superior chemical inertness over the polycrystalline diamond and a higher hardness than a single crystal.…”
Section: Introductionmentioning
confidence: 99%